2015
DOI: 10.3390/nu7095384
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Nutrition and Energy Balance Disorders in Offspring in Later Life

Abstract: The global pandemic of obesity and type 2 diabetes is often causally linked to changes in diet and lifestyle; namely increased intake of calorically dense foods and concomitant reductions in physical activity. Epidemiological studies in humans and controlled animal intervention studies have now shown that nutritional programming in early periods of life is a phenomenon that affects metabolic and physiological functions throughout life. This link is conceptualised as the developmental programming hypothesis whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 136 publications
(166 reference statements)
0
74
0
3
Order By: Relevance
“…Accelerated growth during infancy and increased BMI in early life are known to enhance the risk for obesity [289,290,291], T2DM [292,293], allergy [294,295,296] and cancer later in life [297,298,299]. …”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…Accelerated growth during infancy and increased BMI in early life are known to enhance the risk for obesity [289,290,291], T2DM [292,293], allergy [294,295,296] and cancer later in life [297,298,299]. …”
Section: Milk-mediated Epigenetic Signaling and Diseases Of Civilmentioning
confidence: 99%
“…However, there is now a wealth of experimental and other evidence suggesting that exposure to maternal obesity in fetal life has lifelong effects on the offspring's risk of obesity, which occur before such shared environmental influences act in postnatal life (Reynolds et al . ; Catalano & Shankar ). There are two lines of epidemiological evidence that are important.…”
Section: Early‐life Risk Factorsmentioning
confidence: 99%
“…Apart from a genetic predisposition, part of the observed familial concordance is likely to be explained by a shared environment and patterns of behaviour, including common dietary habits (Fisk et al 2011;Schrempft et al 2016). However, there is now a wealth of experimental and other evidence suggesting that exposure to maternal obesity in fetal life has lifelong effects on the offspring's risk of obesity, which occur before such shared environmental influences act in postnatal life (Reynolds et al 2015;Catalano & Shankar 2017). There are two lines of epidemiological evidence that are important.…”
Section: Maternal Obesitymentioning
confidence: 99%
“…[12][13][14] While genetic and environmental factors both affect the development of obesity, [15][16][17] several studies have shown that in utero and early-life exposure to a high-fat, highsucrose diet (HFSD) produces long-term metabolic effects on offspring with regard to energy balance and glycaemic control. [18][19][20] We used a rodent model that mimics a classic human phenomenon of HFSD exposure during pregnancy that drives hyperphagia and weight gain in offspring to determine whether subsequent juvenile intervention with liraglutide could treat and prevent the onset of obesity and chronic hyperglycaemia during adolescence and early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Different letters within each figure indicate significant difference from each other. Data are given as mean AE SEM life [18][19][20]. As our obesogenic environment continues to drive increasing frequency of maternal obesity, the risk of adolescent obesity and associated metabolic diseases is of severe medical and economic concern.…”
mentioning
confidence: 99%